Severity of curvularia stem blight disease of cassava in West Africa - Msikita, W.; Baimey, H.; James, B.D. (Scientific Societies, 2007)
In diagnostic surveys, Curvularia stem blight affected 9, 13, and 38% of cassava fields, respectively, in Benin, Ghana, and Nigeria. Disease incidence (number of plants with visible symptoms per total sampled) ranged between 0 and 80%, and severity (number of lesions) between 2 and 25 lesions per stem. In greenhouse studies, the fungus inhibited shoot growth depending on the degree of bud colonization, such that when buds were completely colonized, they failed to sprout. Partially colonized buds sprouted, but depending on genotype, overall growth was reduced 20 to 50% compared with healthy stems. Shoot growth for all artificially inoculated cultivars was consistently lower than for the respective noninoculated plants, and they suffered up to 50% leaf abscission. In two field localities, shoot sprouting for cultivars TMS 30572 and Odongbo was reduced 4 to 18% and 26 to 58% compared with noninoculated stems.